DESIGN AND PERFORMANCE RESEARCH ON FLEXURE MICRO ROTARY MECHANISM WITH STRAIGHT CIRCULAR - YANG ManZhi; HUANG YuMei; ZHANG GuangPeng; REN LiJuan; MU WeiYi; YANG XinGang (Jixie qiangdu)
The deformation of static bending was analyzed for uniform beam by the boundary element method.Non-uniform beam was combined with multiple uniform beams by method of system rigid combination without coordinate transformation.Stiffness equation of flexure hinges with straight circular was proposed.A micro rotary mechanism with symmetric drive as well as guiding and transformation was designed based on drive and guiding principles of flexure hinges with straight circular,which is able to make linear motion displacement into rotary displacement,the analysis of degree of freedom about it was given.The analysis of statics with micro rotary mechanism was finished by the finite element method,and the analysis results show that the largest simulation stress of the mechanism is much less than the material allowable stress.The dynamics-free-modal with micro rotary mechanism was analyzed by the finite element,and experiment of the modal analysis was finished,the error between the experimental results and the finite element is less than 6.25%,the analysis results prove that the mechanism has a high the First six order natural frequency and it will not cause resonance in the movement process of the precision rotary system with macro /micro dual-drive.The analysis of performance and experiment shows that micro rotary mechanism has the feature of single-degreefreedom-drive and high reliability,as well as good performance of modal.